The Anatomy of the Temporal and Zygomatic Branches of the Facial Nerve: Application to Crow's Feet Wrinkles. Issue 3 (May 2021) - Ye, Pin; Feng, Xiao-Liang; Yang, Zhi-Hong; Li, Guo-Ping; Sun, Jun; Wu, Hong-Xiang; Chen, Shao-Chun
Abstract : Background: Advances in the understanding of wrinkling crow's feet while improving the safety and efficacy of botulinum toxin type A injection has pointed to drug dispersion in the lateral orbital wrinkles as a cause of adverse events of botulinum toxin type A injection. The purpose of this study is to identify the distribution of temporal and zygomatic branches of facial nerve in the orbicularis oculi muscles. Methods: Anatomical dissection of cadavers was performed in 31 cadavers, 13 females and 18 males, with ages ranging from 20 to 60 years, which of all had been embalmed by 10% formalin solution. The facial nerve was identified within subcutaneous tissue close periorbital region and both traced proximal and distal. Its temporal branch, zygomatic branch, facial and muscular entrance were located and accurately measured relative to established surface landmarks. Results: Dissection of the facial nerve revealed 2 to 6 entrances of the temporal branch into the orbicularis oculi and 1 to 5 entrances of the zygomatic branch into the orbicularis oculi. Concerning the measurements of neural entering points, distance and angle from orbicularis oculi muscle to lateral ocular angle, a distribution map of its muscular entrance and their patterns of distribution were constructed. According to the dense area of the coordinate map, there were 3 points determined as the muscular entrance points to established surface landmarks. Conclusions: An anatomical dissection of cadavers was performed to identify the distribution of temporal and zygomatic branches of the facial nerve in the orbicularis oculi. According to the dense area of the coordinate map, the surface landmarks of 3 points were established as the muscular entrance of the facial nerve (MEF). Abstract : Supplemental Digital Content is available in the text